2022
DOI: 10.1136/bmjopen-2021-056348
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key influences on antibiotic use in China: a systematic scoping review and narrative synthesis

Abstract: IntroductionThe inappropriate use of antibiotics is a key driver of antimicrobial resistance. In China, antibiotic prescribing and consumption exceed recommended levels and are relatively high internationally. Understanding the influences on antibiotic use is essential to informing effective evidence-based interventions. We conducted a scoping review to obtain an overview of empirical research about key behavioural, cultural, economic and social influences on antibiotic use in China.MethodsSearches were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…The results from different methodological approaches converge to enhance their validity; thus our exit survey finding that roughly a quarter of those attending low level health facilities for common RTIs (those most frequently diagnosed in primary care including bronchitis/tracheitis, upper respiratory tract infection, pharyngitis, common cold, pneumonia/ PLOS GLOBAL PUBLIC HEALTH bronchopneumonia and tonsillitis) or UTIs had received antibiotics for previous illness episodes in the past year, and that two-thirds of these were from a hospital pharmacy, concords with our observational data on antibiotic prescribing practices in these facilities. The findings that a further third of clinic patients had obtained antibiotics outside hospital pharmacies, and that nearly 90% of retail pharmacy customers had not previously sought treatment elsewhere, further suggest that over-the-counter purchasing of antibiotics as a first resort for everyday health problems is not uncommon, and this is consistent with previous studies that provide evidence for purchasing of antibiotics without prescription in various settings and population groups in China despite ongoing government efforts to restrict this [25]. From the perspective of patients, frequent antibiotic prescribing for common RTIs in clinics reinforces perceptions that antibiotics are appropriate for common symptoms, indirectly validating their direct purchasing of antibiotics to self-treat such symptoms.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results from different methodological approaches converge to enhance their validity; thus our exit survey finding that roughly a quarter of those attending low level health facilities for common RTIs (those most frequently diagnosed in primary care including bronchitis/tracheitis, upper respiratory tract infection, pharyngitis, common cold, pneumonia/ PLOS GLOBAL PUBLIC HEALTH bronchopneumonia and tonsillitis) or UTIs had received antibiotics for previous illness episodes in the past year, and that two-thirds of these were from a hospital pharmacy, concords with our observational data on antibiotic prescribing practices in these facilities. The findings that a further third of clinic patients had obtained antibiotics outside hospital pharmacies, and that nearly 90% of retail pharmacy customers had not previously sought treatment elsewhere, further suggest that over-the-counter purchasing of antibiotics as a first resort for everyday health problems is not uncommon, and this is consistent with previous studies that provide evidence for purchasing of antibiotics without prescription in various settings and population groups in China despite ongoing government efforts to restrict this [25]. From the perspective of patients, frequent antibiotic prescribing for common RTIs in clinics reinforces perceptions that antibiotics are appropriate for common symptoms, indirectly validating their direct purchasing of antibiotics to self-treat such symptoms.…”
Section: Discussionsupporting
confidence: 86%
“…Interviews with doctors confirmed that while they know these conditions may not all be bacterial, they are concerned about the possibility of secondary infections and, in these settings where patients have low incomes and can rarely afford time off work and domestic duties, they regard patient recovery as most reliably ensured by prescribing broad spectrum antibiotics, in combination with an anti-viral traditional Chinese medicine to cover all possible causes. Previous studies have identified uncertainty about treatment and lower levels of professional training as associated with higher levels of antibiotic prescribing [ 25 ]. Suboptimal antibiotic prescribing is exacerbated by short consultations with limited history-taking and non-disclosure of prior antibiotic consumption by patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed content of the messages is given in Table 1 . Each of these messages was based on the main drivers of excessive antibiotics as identified from our previous studies [ 27 ] and has specific aims. For example, the message, to be sent out on day 1, aims to build trust and assure the patient not to worry about common RTI symptoms and most of which will start to mitigate within a few days and disappear within about 1 week.…”
Section: Methodsmentioning
confidence: 99%